Antibiogram of bacterial isolates from urine at Okhaldhunga Community Hospital: a rural setting in Nepal - Pal , Anjila; Bom, Rabin (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Introduction: Infection of urinary tract is the second most common site of infection after respiratory tract worldwide. The objective of the study is to study the prevalence of positive urine samples and antibiotic susceptibility pattern of the bacterial isolates in Eastern part of Nepal.Method: A total of 210 Mid-Stream Urine (MSU) samples collected from both inpatient and outpatient departments of Okhaldhunga Community Hospital (OCH) were included in the study. Each urine samples were cultured and the antibiogram of isolates were determined as per CLSI guideline.Result: The prevalence of positive culture was found to be 40.9%. Out of which, 82.5% were identified bacteria. The age group with the greatest number of bacterial isolates was 20-30 years. Altogether five different bacteria were identified. Among these, E. coli was the most predominant isolate (76.1%), followed by S. aureus (16.9%) and K. pneumoniae (4.2%). Nitrofurantoin was found to be the most effective drug for the Gram-negative bacilli with a sensitivity of 86.3% while Amoxicillin was least effective showing 87.7% resistance. For Gram positive cocci, Chloramphenicol and Cloxacillin were the most effective and Penicillin was least effective drug showing 84.6% sensitivity and 92.3% resistance respectively.Conclusion: The prevalence of positive urine culture was 40.9%. The most effective antibiotic was Nitrofurantoin. Since the isolates showed high resistance towards Amoxicillin and Doxycycline, antibiotic susceptibility testing of the isolates should be performed time to time to monitor the resistance pattern of the bacteria.